Prior Cardiovascular Treatments—A Key Characteristic in Determining Medication Adherence After an Acute Myocardial Infarction - Campain, Anna; Hockham, Carinna; Sukkar, Louisa; Rogers, Kris; Chow, Clara K; Lung, Thomas; Jun, Min; Pollock, Carol; Cass, Alan; Sullivan, David; Comino, Elizabeth; Peiris, David; et al. (Frontiers in Pharmacology, 2022)
Objective: To investigate long-term adherence to guideline-recommended cardioprotective medications following hospitalization for an acute myocardial infarction (AMI), and identify characteristics associated with high adherence. Methods: An Australian population-based cohort study was used to identify participants who had their first AMI between 2006 and 2014 and were alive after 12 months. Linked routinely collected hospital, service utilization, and prescription medication claims data was used to study adherence over time. Predictors and rates of adherence to both lipid-lowering medication and renin-angiotensin system blockade at 12 months post-AMI was assessed. Results: 14,200 people (mean age 69.9 years, 38.7% female) were included in our analysis. At 12 months post-AMI, 29.5% (95% CI: 28.8-30.3%) of people were adherent to both classes of medication. Individuals receiving treatment with both lipid-lowering medication and renin-angiotensin system blockade during the 6 months prior to their AMI were over 9 times more likely to be adherent to both medications at 12 months post-AMI (66.2% 95% CI: 64.8% to 67.5%) compared to those with no prior medication use (treatment naïve) (7.1%, 95% CI: 6.4% to 7.9%). This was the strongest predictor of long-term adherence even after adjusting for age, sex, education and income. Conclusions: Despite efforts to improve adherence, considerable gaps remain, particularly amongst people who are commencing treatment at the time of their AMI. Health care intervention strategies, supported by enabling policies, are needed to provide support to patients through the initial months following their AMI. Implementation of policies and standards of care are evident during hospital discharge, through continuity of care with a general practitioner and through community pharmacist support.